(untitled) (International Journal of Engineering and Computer Science, 2017)
In the present scenario, the transfer of data is an important thing between one user to another. Data is mainly sent by the distributors which are generally the owner of data to the user which wants the information mainly the trusted third parties. The information sent by the distributor must be confidential and must be shared by a secure way. Some times during sharing of data, multiple copies of information is generated by different parties which cause a huge amount of loss, this is known as data leakage. To prevent this leakage of data one must put measures in order to detect the leakage in an early stage. The purpose of this paper to discuss data leakage and its prevention by various watermarking techniques.